Skull Base Metastasis From Occult Renal Cell Carcinoma. Issue 3 (May 2018) - Golinelli, Gloria; Toso, Andrea; Rosa, Maria Silvia; Valletti, Paolo Aluffi; Pia, Francesco
Abstract : Abstract: Skull base metastases are extremely rare. The authors report a case of a 65-year-old man who presented with a headache and diplopia secondary to a skull base metastasis from occult renal cell carcinoma. Since there were no other systemic metastases, radical nephrectomy and radiotherapy of the unresectable skull base location were performed. He subsequently received immunotherapy with sunitinib, everolimus, and sorafenib with local and systemic control of the disease after 53 months from surgery. When metastasis is unresectable radical nephrectomy and radiotherapy aimed at the metastasis may be of benefit improving quality of life. Immunotherapy may provide alternative treatment strategies improving the outcomes of patients affected by this rare pathology with historically poor prognosis.